Characterization of microoptical components - Lindlein, Norbert (2003 Conference on Lasers and Electro-Optics Europe, CLEO/EUROPE 2003, 2003)
Microoptical components are more and more important in technical applications due to the miniaturization of optical systems for communication, sensors, visualization devices and other purposes. Since the quality in the fabrication of an optical element cannot be better than the measurement accuracy with which the element can be tested, it is very important that also microoptical components can be characterized with sufficient accuracy. In this paper several measurement devices for microoptical components like rotationally symmetric microlenses and cylindrical microlenses will be presented. © 2003 IEEE.